MORTAR WITH SUBSTITUTE THE NATURAL AGGREGATE BY THE RESIDUES THE CRUSHING THE GRANITE - Santos, Robson Arruda dos; Lira, Belarmino Barbosa; Ribeiro, Ana Carolina Marinho (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611707238 The construction industry consumes many natural resources and generating waste is great. There is a bigproblem related to their treatment, and an alternative to its reuse as a substitute for natural materials,such as the production of mortar and concrete. This paper aims to study the reuse of tailing from crushingof granite as aggregate in mortar. The residues were tested according to the ABNT fine aggregate used inconstruction. Two traits were determined with the total replacement of natural sand residue in the studyand performed strength tests on specimens, according to NBR 13279, and the study of the influence of theresidue in appearance and water consumption. It was found that substitution reflected positively on theresistance to compression and bending of the mortar. However, it is noteworthy that to obtain anaggregate with good performance is necessary to classify the material, necessitating the use of classifiersin order to remove the finer and coarser fractions allowing their applications, an acceptable performance.